John Marincola, Authority and Tradition in Ancient Historiography, Cambridge U.P., 1997, XVI + 361 pp. (Minerva, 2019)
Review: John Marincola, Authority and Tradition in Ancient Historiography, Cambridge U.P., 1997, XVI + 361 pp.